Synthesis and Characterization of some Mercury(II) Complexes with Phosphine Oxide, Sulphide and Mixed Ligands - A. AL-Jibouri, Subhi; J. Al-Hayaly, Lama'an; A.K. Al-Allaf, Talal (Asian Journal of Chemistry, 2010)
A series of mercury(II) complexes of the general formula HgX2· L (X=Cl–, Br–, I–; L=(Ph2PO)2(CH2)n, n=1 or 2; Ph2(O)CH2PPh2; (Ph2PS)2(CH2)n, n = 1, .2 or 3 and Ph2P(O)CH2P(S)Ph2, have been prepared and characterized on the basis of their elemental analysis and IR spectroscopy.